A 0.6-V 8.3-ENOB asynchronous SAR ADC for biomedical applications - 宋焱 薛仲明 严鹏程 张珏颖 耿莉 (Journal of semiconductors, 2014)
A microwatt asynchronous successive approximation register （SAR） analog-to-digital converter （ADC） is presented. The supply voltage of the SAR ADC is decreased to 0.6 V to fit the low voltage and low power require- ments of biomedical systems. The tail capacitor of the DAC array is reused for least significant bit conversion to decrease the total DAC capacitance thus reducing the power. Asynchronous control logic avoids the high frequency clock generator and further reduces the power consumption. The prototype ADC is fabricated with a standard 0.18 μm CMOS technology. Experimental results show that it achieves an ENOB of 8.3 bit at a 300-kS/s sampling rate. Very low power consumption of 3.04 μW is achieved, resulting in a figure of merit of 32 fJ/conv.-step.